Changes of landscape structure and soil production function since the 18th century in north-west saxony - Baude, Mike; Meyer, Burghard C. (Journal of Environmental Geography, 2010)
The objectives of this paper are (1) to reconstruct time series of the historical and current landscape structures based on historical documents and serial cadastral maps, (2) to analyse the changes of agricultural production function by the application of historical soil assessments and (3) to analyse the connections between landscape structure and production function in reference to the social and economic driving forces. The case study area is today an intensively-used agricultural landscape located nearby Taucha-Eilenburg (NW-Saxony), Germany. Arable landscapes in Germany are changing with increasing dynamics: valuable structures and landscape functions of the traditional and multifunctional landscape were lost. New landscape structures replaced the traditional ones slowly or sometimes also in short time steps. Therefore, this paper focuses on the changes of landscape structures and that of the soil production function induced by land use since the 18th century. The changes are analysed on the basis of historical and serial cadastral maps and documents by covering four time steps from 1750 to 2005. The historical maps were scanned, geo-referenced and digitalised in GIS. Thus, quantitative analysis of landscape structure changes on parcel level is enabled. The production function is explicitly reconstructed on the basis of the Prussian Taxation of the real estate of 1864 (Preußische Grundsteuerbonitierung) and The German Soil Taxation (Reichsbodenschätzung) of 1937. Changes observed on the serial cadastral maps were linked with the social and economical driving forces and the soil production function. Moreover, there is a high demand for the development of methodologies to analyse and to assess time series of landscape structures, land use and landscape functions in the historical context of landscape development.